THE INCREASING THE STUDENTS’ MOTIVATION, SPEAKING ABILITY THROUGH INTEGRATIVE ORIENTATION AT THE FIRST GRADE OF SMA MUHAMMADIYAH 1 METRO - Aditia Armadan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2019)
English is an international language which is learned by many people to catch up with the development of the world, especially in education, science, and technology. Therefore, it is very important to master it in order to be able to perform smooth communication with other people from other countries. Realizing the importance of English, the government of Indonesia has declared English as the first foreign language which is taught in Indonesia, starting from elementary school until university levels. The research is classroom action research (CAR), the aim of this research is to find the result of the implementing of integrative orientation. The first previous research is “ The Correlation Between The Students’ Motivation And The Students’ English Learning Achievement at the second semester of SMA PGRI 1 Bumi Nabung by Reza Pradana”. In this research found the information of the english learning achievement toward students’ motivation. The researcher assumed that motivation corelating the students’ achievement, in other words if the students’ want to get the good achievement especially english learning so the students’ must have good motivation too. It can be concluded that any corelation of motivation toward english learning achievement. This research, the researcher will use the Classroom Action Research (CAR), because classroom action research was one of the effort to increase the teaching program quality in all educational level intend Senior High School. Action research will be done the researcher or teacher as manager of teaching program. Classroom action research is mean that the teacher can know what do and dissolve the problem in their class